PENGEMBANGAN BAHAN AJAR INTERAKTIF DENGAN BERBANTUAN HEYZINE FLIPBOOKS UNTUK MEMBANGUN CHARACTER OF CITIZENS SISWA KELAS 2 SEKOLAH DASAR - Yeni Pusnawati; Oktaviani Adhi Suciptaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop interactive teaching materials with the help of Heyzine flipbooks to build character of citizens in grade 2 elementary school students. The research method used is R & D research with the ADDIE model which consists of 5 stages, namely; Analysis, Design, Development, Implementation and Evaluation. The research subjects were class 2 teachers and class 2 students at UPT SD Negeri Tumpakkepuh 02. The instruments used in this research were interview and questionnaire guidelines. Data analysis is used by calculating the percentage of results from validation by material experts, media experts and student responses. Based on the needs analysis that has been carried out, teachers and students really need interactive teaching materials assisted by Heyzine flipbooks. The validation results from media experts obtained 78.82% which was categorized as feasible. The material expert validation results obtained a score of 93.33% in the "very appropriate" category. Overall, the results of the small-scale trials obtained an average score of 92%, which is in the very feasible category.